The Relationship Between Job Demands and Self-Efficacy on Academic Stress Levels in Working Students in Sidoarjo City : Hubungan antara Tuntutan Pekerjaan dan Efikasi Diri terhadap Tingkat Stres Akademik pada Mahasiswa yang Bekerja di Kota Sidoarjo - Arizatun Nisa'; Widyastuti Widyastuti (Universitas Muhammadiyah Sidoarjo, 2025)
This study aims to examine the relationship between job demands and self-efficacy with academic stress among working university students in Sidoarjo. A quantitative approach was employed, involving 204 respondents who were either full-time or part-time working students. The sample was selected using a convenience sampling technique. Data were collected through a Likert-scale questionnaire covering three main aspects: academic stress, job demands, and self-efficacy. All instruments had undergone validity and reliability testing. Data analysis was conducted using multiple linear regression with the assistance of SPSS version 25.0. The results showed that both job demands and self-efficacy were significantly related to academic stress. Job demands had a positive relationship, while self-efficacy had a negative relationship with the level of academic stress among students. The coefficient of determination (R²) was 0.869, indicating that 86.9% of the variation in academic stress could be explained by the relationship between these two variables and academic stress. The regression model met all classical assumption tests, thus was considered valid. These findings highlight the importance of managing job demands and strengthening self-efficacy in reducing academic stress among working students.Highlight : Job demands positively correlate with academic stress — higher workload leads to higher stress levels. Self-efficacy acts as a protective factor — students with stronger belief in their abilities report lower stress. Regression model explains 86.9% of stress variation — indicating strong predictive value from both variables. Keywords : Academic Stress, Job Demands, Self-Efficacy, Working Students, Regression Analysis